Uniwersalny wymiar miłości Boga według J 3,16 - Kubiś, Adam (Verbum Vitae, 2013)
John 3:16 is undoubtedly one of the best known and most beloved verses in all of Scripture. At the same time, when ripped from its literary, historical and theological contexts as it so often is, this verse can become merely a pious, sentimental saying bereft of its true, earth-shaking message. Thus this study provides not only an exegetical analysis of the verse, but also the exposition of its various contexts: literary (the interchange between Jesus and Nicodemus on the entrance into the kingdom of God), historical (the destruction of the Jerusalem temple and the worldwide mission of the early Church) and theological (the OT, NT and John’s Gospel concepts of God’s universal love). God’s love for the world, and the salvific mission flowing from it, are most beneficially viewed from a salvation-historical perspective, as the core Trinitarian outreach in which all are called to take part by putting faith in Jesus.